Experimental study of confined masonry walls against perpendicular loads by tsunami - Camacho Roque, Chrysler (2024)
The high seismic activity on the Peruvian coast carries a potential risk of tsunamis that could affect the Peruvian coast, causing damage to people and structures. According to studies carried out by CISMID and Fondecyt, approximately 83% of the houses in Metropolitan Lima and Callao are made of masonry, mainly due to its low economic cost. The present experimental study aims to study the behavior of confined masonry walls under the action of perpendicular loads to the wall produced by the impact of tsunami waves, which is a field of research where it is still necessary to delve deeper with experimental studies of the structures under equivalent tsunami loads. As part of the experimental study, 2 confined masonry walls were built, which were tested under the action of perpendicular loads applied by means of hydraulic jacks with a force control simulating the forces induced by a tsunami. From the experimental test, a failure was obtained by bending perpendicular to the plane of the main wall reaching a total load equivalent to a maximum height of the wave train of 3.95 m for a distortion of 1/75 at the level of the lightened slab. In addition, the limit deformation for confined masonry structures indicated in the Peruvian Standard E030 was reached for a load equivalent to a maximum height of the wave train of 3.00